Ответ:
Объяснение:
((u²-4u+16)/(16u²-1) ·(4u²+u)/(u³+64) -(u+4)/(4u²-u)) ÷7/(u²+4u) -(20u+13)/(7-28u)=((u²-4u+16)/((4u-1)(4u+1)) ·u(4u+1)/((u+4)(u²-4u+16)) -(u+4)/(u(4u-1))) ·u(u+4)/7 -(20u+13)/(7(1-4u))=(u/((4u-1)(u+4)) -(u+4)/(u(4u-1))) ·u(u+4)/7 -(20u+13)/(7(1-4u))=(u²-(u+4)(u+4))/(u(4u-1)(u+4)) ·u(u+4)/7 -(20u+13)/(7(1-4u))=(u²-(u²+8u+16))/(7(1-4u)(4u-1)) -(20u+13)(4u-1)/(7(1-4u)(4u-1))=(8u+16-20u-13)/(7(1-4u)(4u-1))=(3-12u)/(7(1-4u)(4u-1))=3(1-4u)/(7(1-4u)(4u-1))=3/(28u-7)=3/(7(4u-1))
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
((u²-4u+16)/(16u²-1) ·(4u²+u)/(u³+64) -(u+4)/(4u²-u)) ÷7/(u²+4u) -(20u+13)/(7-28u)=((u²-4u+16)/((4u-1)(4u+1)) ·u(4u+1)/((u+4)(u²-4u+16)) -(u+4)/(u(4u-1))) ·u(u+4)/7 -(20u+13)/(7(1-4u))=(u/((4u-1)(u+4)) -(u+4)/(u(4u-1))) ·u(u+4)/7 -(20u+13)/(7(1-4u))=(u²-(u+4)(u+4))/(u(4u-1)(u+4)) ·u(u+4)/7 -(20u+13)/(7(1-4u))=(u²-(u²+8u+16))/(7(1-4u)(4u-1)) -(20u+13)(4u-1)/(7(1-4u)(4u-1))=(8u+16-20u-13)/(7(1-4u)(4u-1))=(3-12u)/(7(1-4u)(4u-1))=3(1-4u)/(7(1-4u)(4u-1))=3/(28u-7)=3/(7(4u-1))